Percutaneous Rotational Mechanical Atherectomy Plus Thrombectomy Using Rotarex S Device in Patients With Acute and Subacute Lower Limb Ischemia: A Review of Safety, Efficacy, and Outcomes - Loffroy, Romaric; Falvo, Nicolas; Galland, Christophe; Fréchier, Léo; Ledan, Frédérik; Midulla, Marco; Chevallier, Olivier (Frontiers in Cardiovascular Medicine, 2020)
Acute and subacute ischemia of the limbs is associated with high risk of limb loss and severe life-threatening complications, representing a major cause of peripheral ischemia and limb amputations. Despite a lack of clear therapeutic recommendations, surgical treatments such as thrombectomy or bypass and/or catheter-directed thrombolysis (CDT) have been front-line procedures in both acute and subacute limb ischemia but each therapy is associated with a significant incidence of morbidity and mortality. Such situations demand fast restoration of adequate flow, in order to preclude limb loss and other complications. Percutaneous mechanical atherectomy plus thrombectomy (MATH) represents a minimally invasive option for rapidly recanalizing thrombus-containing lesions whatever the age of thrombus. Indeed, many chronic patients may present with critical limb ischemia, with thrombus-containing occlusions triggered by underlying atherosclerotic lesions. MATH offers various advantages over CDT and surgery, with lower invasiveness, faster reperfusion, and the opportunity to immediately treat the underlying lesions, with a lower rate of bleeding complications and no need for intensive care unit stay. Currently, several mechanical thrombectomy devices are offered as an alternative therapy and can be divided into pure rotational MATH systems and rheolytic thrombectomy devices. The only pure rotational MATH device currently available on the market is the RotarexS device. We aimed to review contemporary clinical data regarding the safety, efficacy and outcomes of MATH therapy using RotarexS catheter in acute and subacute thrombus-containing arterial lesions of lower limbs. Future perspectives of RotarexS MATH treatment and cost-effectiveness of its routine use will be also discussed.